Borys Shcherba. Activities of the Museum-Archive of the transition period as an example of an attempt to revive national life in occupied Kyiv in 1942 : Borys Shcherba. Activities of the Museum-Archive of the transition period as an example of an attempt to revive national life in occupied Kyiv in 1942 - Shcherba, Borys (Young Scholars Grinchenko – Seton International Journal, 2022)
Borys Shcherba. Activities of the Museum-Archive of the transition period as an example of an attempt to revive national life in occupied Kyiv in 1942